2023
DOI: 10.1192/j.eurpsy.2023.23
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to eating disorder care: A European multicenter study

Abstract: Background. To assess barriers and facilitators in the pathways toward specialist care for eating disorders (EDs).Methods. Eleven ED services located in seven European countries recruited patients with an ED. Clinicians administered an adapted version of the World Health Organization "Encounter Form", a standardized tool to assess the pathways to care. The unadjusted overall time needed to access the ED unit was described using the Kaplan-Meier curve.Results. Four-hundred-nine patients were recruited. The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…These data further indicate the importance of pro viding sufficient resources to enable early diagnosis and treat ment, and of reducing barriers and delays to treatment access in young people 82,83 . For this purpose, services and policy makers should look at family and general practitioner education 31 , and the strict division still existing in many settings between child and adult mental health services should be overcome 34,84,85 . Among interventions for EDs included in more than one study, treatments with a primary nutritional component were associated with the highest rates of overall recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data further indicate the importance of pro viding sufficient resources to enable early diagnosis and treat ment, and of reducing barriers and delays to treatment access in young people 82,83 . For this purpose, services and policy makers should look at family and general practitioner education 31 , and the strict division still existing in many settings between child and adult mental health services should be overcome 34,84,85 . Among interventions for EDs included in more than one study, treatments with a primary nutritional component were associated with the highest rates of overall recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Access to treatment for EDs is inadequate, with only 20 25% of individuals receiving professional consultation for their symp toms 29 . Barriers to treatment access include stigma, lacking insight into the illness, shame, scarce availability of evidence based in terventions, and fragmented or underfunded health services 30,31 , which contribute to low recovery rates and frequent chronicity 32 . The complexity of EDs requires a multidisciplinary treatment ap proach to address psychological, environmental, nutritional, be havioral and physical problems, as well as mental health comor bidities 33,34 .…”
mentioning
confidence: 99%
“…The studies also showed significant variation in composition: specific professionals, such as psychiatrists and nurses, were inconsistently outlined. This contrasts with the knowledge that EDs are complex diseases that need treatment by a wide range of healthcare figures [ 110 ].…”
Section: Discussionmentioning
confidence: 97%
“…Initial findings have demonstrated the helpfulness of including people with lived experience of a specific health condition such as videos of peers in ED recovery in reducing stigma and shame around the illness, suggesting that this could be useful in addressing denial (Ali et al., 2022; Linardon et al., 2021; Sheens et al., 2016). However, additional research is needed to explore the role of peer‐to‐peer support in assisting people with eating disorders (Ali et al., 2015), especially considering recent research which found that family members or partners play a more significant role in the help‐seeking process than peers (Monteleone et al., 2023). Overall, further research is needed to identify whether perceived barriers can be changed with interventions and more importantly whether this will result in increased help‐seeking behaviour for ED symptoms over time.…”
Section: Discussionmentioning
confidence: 99%